Plane of Nutrition of Marwari Ewes in Different Seasons Grazing on Natural Range Pasture of the Arid Region - Mali, P C; Patnayak, B C; Bedekar, A R (Annals of Arid Zone, 2016)
Nutritional status of Marwari ewes grazing on natural range pasture of the arid region was studied by using indicator technique. Chromic oxide was used to estimate faecal output and lignin as an internal indicator to estimate intake and digestibility. Ingested forage samples were collected from the mouth of the animals for analysis of proximate principles. Intake measurements were taken in August, November, February and May representing four seasons covering January to March, April to June, July to September and October to December and designated as season 1, 2, 3 & 4, respectively. The crude protein percentage of the ingested forage was highest (9.47%> and crude fibre (25.97%) lowest during season 3. The acid detergent fibre was the highest (SO%) and TDN value of the ingested forage was the lowest during season 4 as compared to other seasons. The DCP value of the ingested herbage varied from 0.84% during season 1 to 1.6% during season 3 due to very low digestibility coefficient for protein. Dry mailer consumption was the highest during season 3 and lowest during season 2 varying from 3.0 to 3.4 kg per 100. kg body weight. The TDN intake varied from 339 g/day to 440 g/day in different seasons. Due to low digestibility of protein, CF and NFE the TDN consumption per unit metabolic size was the lowest during' season 4 as compared to that of other seasons. Although crude protein intakes were adequate (49 to 93 g/day), the digestibility coefficient values for crude protein were very low (14 to 17%) amounting to DCP intake/animal/day of only 7 to 8 g during season 1 and 2, and 14 to 15 g during season 3 and 4.These values are much lower than expected. It may be that in a low protein regime the, animals recycle the nitrogen and meet their nitrogen requirement. It could also be possible that in the grazing situation ingestion of soil/sand may lead to' increase in metabolit faecal nitrogen through denudation of mucous membrane which gives high nitrogen percentage in the faeces resulting in low apparent digestibility of protein.